Case Study: Multimodal Approach As an Alternative for Effective English Learning and Teaching in Polytechnic of Energy and Mineral - Februati, Bernadin Maria Noenoek; Dewa, Dominica Maria Ratna Tungga (Riviera Publishing, 2025)
The effectiveness of English Learning and Teaching (ELT) is primarily evaluated by students' proficiency in communicating in English, covering speaking, listening, reading, and writing skills. At PEM Akamigas, this proficiency is vital for effective communication within the energy and mineral resources fields. However, classroom observations reveal a lack of student attention and engagement, particularly among Gen-Z students who dominate the institution. Characterized by their digital nativity, Gen-Z students exhibit shorter attention spans and a preference for interactive, multimedia content, which traditional teaching methods fail to address. Hence, this research explores the implementation of a multimodal approach as a solution. By integrating text, audio, visuals, and interactive digital tools such as Kahoot!, virtual reality, and gamification, the approach caters to the diverse learning styles of Gen-Z students. Additionally, collaborative tools like Google Docs and instant feedback mechanisms foster active participation and engagement. While previous studies highlight multimodal benefits in general education, this research fills a gap by focusing on technical and energy and mineral resources contexts. It examines how a multimodal approach enhances student attention, engagement, and achievement in ELT at PEM Akamigas, aiming to bridge traditional methods with Gen-Z's digital-first learning preferences. This study answers whether and how multimodal strategies improve ELT effectiveness in this specialized field.